Efficacy of interferon alpha for the treatment of hospitalized patients with COVID-19: A meta-analysis - Buchynskyi, Mykhailo; Kamyshna, Iryna; Lyubomirskaya, Katerina; Moshynets, Olena; Kobyliak, Nazarii; Oksenych, Valentyn; Kamyshnyi, Aleksandr (Frontiers in Immunology, 2023)
Introduction: IFN-α intervention may block SARS-CoV-2 replication and normalize the deregulated innate immunity of COVID-19. Aim: This meta-analysis aimed to investigate the efficacy of interferon IFN-α–containing regimens when treating patients with moderate-to-severe COVID-19. Material and methods: PubMed, SCOPUS, and ClinicalTrials.gov were searched from inception to 15 January 2022. A systematic literature search was conducted by applying relevant terms for ‘COVID-19’ and ‘interferon-α’. The primary outcome enclosed the all-cause hospital mortality. The secondary outcomes constituted the length of hospital stay; hospital discharge; nucleic acid negative conversion. Results: Eleven studies are enclosed in the meta-analysis. No significant difference in the all-cause mortality rate was found between the study and control groups (OR 0.2; 95 % CI 0.05-1.2; I2 = 96%). The implementation of interferon did not influence such outcomes as the length of hospital stay (OR 0.9; 95 % CІ, 0.3-2.6; I2 =91%), nucleic acid negative conversion (OR 0.8; 95 % CI, 0.04-17.2; I2 =94%). Nevertheless, IFN-α treatment resulted in a higher number of patients discharged from the hospital (OR 26.6; 95 % CІ, 2.7-254.3; I2 = 95%). Conclusions: Thus, IFN-α does not benefit the survival of hospitalized COVID-19 patients but may increase the number of patients discharged from the hospital.